Estrategias desde el diseño de servicios para vincular transportadores de alimentos a plataformas digitales en Colombia (2020)
The following project is a design proposal that seeks areas of action to solve the issue of low numbers of food transporters using the new digital cargo platforms. This proposal offers new digital platforms a design-based service strategy on the understanding and needs of the social processes that are part of the Colombian cargo community, this is done by articulating parts of the communities traditional dynamics, to the new digital model. The proposal is based on three areas of action that were investigated and prototyped with representatives of the Bogotá cargo community, and whose objective is to guide changes in the platforms backend and services offered, with the purpose of using these changes as a way to attract new users of the cargo community to be part of the new apps.